Implantação de um novo layout de uma linha de montagem de motocicletas estruturados a partir da metodologia MASP e ferramentas Lean manufacturing - OLIVEIRA, Edyones Barros de (Universidade Federal do Pará, 2021)
This study aims to approach the implementation of a new layout of manufacturing process for high displacement motorcycles using the MASP methodology and Lean Manufacturing tools as a facilitator to adapt to the market oscillation. The research was carried out in a motorcycle industry located in the Free Trade Zone of Manaus, using the PDCA method (Plan, Do, Check, Action) for the feasibility after SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in which the focus of actions of the project was defined. As a result, benefits were presented, such as: flexibility to increase production capacity due to the new layout arrangement and 67% reduction of Work In Process that made 25% of the total industrial area viable; versatility in the assembly process due to increased training of operators to produce all models; 5,5% reduction of the operator quantity keeping the same productive capacity; a reduction of at least 25% in the investment needed to implement new products, reaching up to 60% depending on the motorcycle in question, enabling the approval of the launch of four models in the last six months and avoiding an increase of 51.25% in value the asset chart; annual reduction of R$ 80,000.00 in costs with spare parts and preventive maintenance service; 15% reduction in electricity consumption; and a 5% decrease in line stoppage due to the limitation to change the production plan. With that, it provided greater brand competitiveness in the Brazilian market even when compared to other brands in thex same segment that have already presented studies of process optimization focused on the Lean Production principle but limited to the manufacturing benefits.